Effects of Zinc and Nitrogen on Yield Components of Five Flax Genotypes (Global Journal of Science Frontier Research, 2013)
Flax is one of the earliest plants that has been domesticated by humans. Due to high amounts of omega-3 fatty acid, its cultivation and consumption is increasing as a healthy oil resource. In nutritional point of physiology zinc and nitrogen are two important elements in plant biosynthesis. So in this experiment, effects of three levels of nitrogen (40, 60 and 80 kg/ha) and two levels of zinc sulfate (control and 3/1000) on five flax cultivars in split factorial based on randomized complete block design was investigated. The results showed that genotypes in terms of height, capsul number, seed yield and biological yield revealed significant differences (P kg nitrogen and (3/1000) zinc sulfate spray.
Keywords: flax; oil plants; yield; zinc sulfate